Effect of elevated temperature and carbon dioxide on maize genotypes health index. (October 2019) - Mina, Usha; Kumar, Ram; Gogoi, Robin; Bhatia, Arti; Harit, R.C.; Singh, Deepak; Kumar, Amit; Kumar, A.
Highlights: Indicators identified for assessing maize genotypes response under elevated temperature and carbon dioxide concentration [CO2 ]. Crop Health Index (CHI) formulated for maize genotypes response under elevated temperature and [CO2 ]. Stress tolerant and susceptible maize genotype exhibited high and low CHI respectively. CHI value indicated more tolerance to elevated temperature and [CO2 ] in PEHM 5 as compared to CM 119. Abstract: Reports on the adverse impacts of climate change on growth and productivity of crops due to elevated temperature and carbon dioxide concentration ([CO2 ]) is persistently raising the need for development of tools to assess response of crops to climate change factors. In the present study, Crop Health Index (CHI) was generated for response of maize genotypes under elevated temperature and [CO2 ]. Under field condition, in open top chambers PEHM 5 and CM 119 maize genotypes throughout their crop growth period were treated with two [CO2 ] levels: ambient (400 ppm) and elevated (550 ± 20 ppm) and three temperature levels: ambient, ambient +1.5 °C and ambient +3 °C. Response of maize genotypes to temperature and [CO2] was monitored through thirteen stress indicator parameters – morphological, physiological and biochemical at three growth stages – vegetative, tasselling and dent. Yield for both genotypes under each treatment was recorded at maturity. The data was used to delineate minimum dataset (MDS) responsive to combinations of temperature and [CO2 ] treatments through principal component analysis (PCA). Out of thirteen indicators, total dry biomass, total phenol content, relative leaf water content and photosynthetic rate was found to be having higher frequencies for MDS at all three stages. Parameters selected under MDS were transformed to get linear score ( Si ) using a linear scoring method and weighing factor ( Wf ) value. Then, average linear score ( S i ¯ ) [(Si)] and average weightage score ( W i ¯ ) were used to generate CHI. Results indicated that CHI for maize genotypes under different treatments varied between 0.14–0.93. Average CHI under different treatment was significantly related with yield of PEHM 5 and CM 119 and R2 was 0.82 and 0.90, respectively. It was observed that increase in temperature had detrimental effect on CM 119 and PEHM 5 genotypes with minimum average CHI of 0.20 and 0.53, respectively. On the contrary, elevated [CO2 ] was found to be having amelioration effect on CM 119 and PEHM 5 genotypes to adverse effect of elevated temperature with highest average CHI of 0.46 and 0.75, respectively.